2016
DOI: 10.1016/j.soilbio.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-oxidizing bacteria are more responsive than archaea to nitrogen source in an agricultural soil

Abstract: In the majority of agricultural soils, ammonium (NH +) is rapidly converted to nitrate (NO 3-) in the biological ammonia and nitrite oxidation processes known as nitrification. The often rate-limiting step of ammonia oxidation to nitrite is mediated by ammonia oxidizing bacteria (AOB) and ammonia oxidizing archaea (AOA). The response of AOA and AOB communities to organic and conventional nitrogen (N) fertilizers, and their relative contributions to the nitrification process were examined for an agricultural si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
116
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(146 citation statements)
references
References 66 publications
23
116
3
4
Order By: Relevance
“…6), confirming similar results obtained from various agricultural soils (Phillips et al 2000;Chu et al 2007;Ouyang et al 2016). It has been suggested that Nitrosospira cluster 3 often outcompeted other Nitrosospira under fertile soil conditions (Tourna et al 2010).…”
Section: Aoa-otu7 (256bp)supporting
confidence: 84%
“…6), confirming similar results obtained from various agricultural soils (Phillips et al 2000;Chu et al 2007;Ouyang et al 2016). It has been suggested that Nitrosospira cluster 3 often outcompeted other Nitrosospira under fertile soil conditions (Tourna et al 2010).…”
Section: Aoa-otu7 (256bp)supporting
confidence: 84%
“…However, by characterising the conserved amoA gene, which encodes a subunit of the ammonia monooxygenase (AMO), it has been observed that the populations of ammonia oxidisers are largely controlled by soil type, NH 4 + concentration, pH and water content (Nicol et al 2008;Di et al 2009;Chen et al 2010;Norton and Stark 2011). In ammoniumrich soils, AOB abundance and activity increased whereas AOA abudance is unaffected or inhibited in response to a high concentration of ammonium fertilisers (Jia and Conrad 2009;Di et al 2009;Di and Cameron 2011;Sterngren et al 2015;Ouyang et al 2016). In unfertilised or acidic soils, AOA abundance and metabolic activity are much higher than those of AOB (Offre et al 2009;GubryRangin et al 2010;Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that AOB is more sensitive to 1-octyne, a C8 alkine inhibitor, compared with AOA (Taylor et al 2013(Taylor et al , 2015. Moreover, Lu et al (2015) and Ouyang et al (2016) distinguished AOB and AOA contribution to nitrification by using 1-octyne in soil microcosm incubation and found that 1-octyne selectively inhibited AOB growth rather than AOA in forest and arable soils. Therefore, we could use 1-octyne to assess the relative contribution of AOB and AOA to N 2 O emission from two different arable soils.…”
Section: Introductionmentioning
confidence: 99%
“…A series of ecological researches verified that AOA were more suitable to live with low substrate concentrations in different habitat types. In an agricultural soil whose nitrification rate was dominated by AOA out of low ammonium availability, ammonium fertilizers stimulated AOB activity and community more strongly than AOA (Ouyang et al, 2016). In a temperate forest soil where AOA significantly contribute to ammonia oxidation, substrate availability limits nitrification by AOB.…”
Section: Ammonia Concentration Leading To the Niche Segregation Of Aomentioning
confidence: 93%
“…Some evidences showed that those environmental factors might have interrelationship (Figure 2). Strong ecological coherence was reflected between phylogeny and pH, or phylogeny and organic matter content for terrestrial Thaumarchaeota (Oton et al, 2016). This implied that pH and organic matter content might have some internal direct or indirect connection.…”
Section: Potential Interrelationship Among Environmental Factorsmentioning
confidence: 94%